2016
DOI: 10.13189/saj.2016.040102
|View full text |Cite
|
Sign up to set email alerts
|

High School Sport Participation: Does It Have an Impact on the Physical Activity Self-efficacy of Adolescent Males?

Abstract: In this study, the association between physical activity participation and selfefficacy for physical activity was measured in adolescent males. Also, the possibility that self-efficacy levels differed between school sport participants and non-school sport participants was explored. The results of the Spearman's p test showed a moderate positive, and significant correlation between PAQ-A and SEPAQ scores, r(113) = .571, p < .01. The regression analysis showed that PAQ-A score significantly predicted SEPAQ score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…The positive impact of PA on self-efficacy in the study is not surprising, and the finding is in line with the previous studies [ 29 , 30 , 31 ]. Also being consistent with the existing literature, self-efficacy has a negative impact on AP [ 11 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The positive impact of PA on self-efficacy in the study is not surprising, and the finding is in line with the previous studies [ 29 , 30 , 31 ]. Also being consistent with the existing literature, self-efficacy has a negative impact on AP [ 11 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Self-efficacy refers to beliefs in one’s capabilities to organize and execute the courses of action required to produce given attainments [ 26 , 27 ]. Research has found that PA was positively related to self-efficacy in adolescents and older adults [ 28 , 29 , 30 ]. The positive relationship between PA and self-efficacy was also found in college students, and the higher PA intensity, the higher level of self-efficacy [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of activity psychology, the positive benefits of physical activity for mental health have been widely recognized (Sexton et al, 1989;Xiao, 2015). Among these benefits, physical activity plays a crucial role in improving selfefficacy (Downs and Strachan, 2016). After vigorous running or cycling, an individual's self-efficacy increases (McAuley et al, 1995).…”
Section: Physical Activity and Self-efficacymentioning
confidence: 99%
“…CS exerts a completely mediating effect, in which NC plays a mediating role while the PC does not exert a significant mediating effect. The effect of PA on improving CS is probably because PA improves the level of psychological capital appreciation (PCA) and body-esteem of college students [97,98]. Performing moderate-to-high intensity PA can enhance the adolescent's sense of self-efficacy, which optimizes their CS [77].…”
Section: Discussionmentioning
confidence: 99%